Kajian Etnosains pada Makanan Tradisional Buak Tat sebagai Sumber Belajar IPA - Liska Handayani; Afifah Nurul Ramadanti; Hania Putri Zalianti; Intan Mara Claudia; Nila Oktavia; Meilinda Meilinda; Berti Yolida; Rini Rita T Marpaung (STKIP Subang, 2026)
This study aimed to analyze the material change concepts embedded in the process of making Buak Tat, a traditional food from Lampung, from an ethnoscience perspective and to examine its potential as a science learning resource. A descriptive qualitative method with an ethnoscience approach was employed due to the limited studies on Lampung traditional foods as ethnoscience-based learning resources. Data were collected through interviews with a Buak Tat producer and analyzed by identifying local knowledge and reconstructing it into scientific concepts. The results showed that the preparation of Buak Tat involves ingredient preparation, flour sieving, dough preparation, filling preparation, dough shaping, baking, and cooling. These stages contain various material change concepts, including physical changes during ingredient preparation, sieving, dough preparation, sugar dissolution, dough shaping, and cooling, as well as chemical changes during filling preparation and baking through protein denaturation, gel formation, caramelization, and Maillard reactions. Local knowledge used by the community is reflected in sensory indicators such as color, aroma, texture, and viscosity, which correspond to scientific concepts related to the properties and changes of matter. Therefore, Buak Tat has potential as an ethnoscience-based science learning resource that supports contextual learning and local wisdom preservation.